The Holistic Stewardship Framework: Revolutionizing Management Education - Machado, Marcelo; Eva, Maryanne; Saikia, Kavya (European Journal of Sustainable Development, 2025)
Universities and business schools are expected to play a crucial role in addressing modern challenges, given their key role in society and their vital function in generating and sharing knowledge. Traditional management education, often siloed and focused on economic feasibility, falls short in preparing leaders for today’s complex landscape. This paper proposes the Holistic Stewardship Framework, a transformative approach to management education. Grounded in corporate sustainability, this paradigm adopts the United Nations Principles of Responsible Management Education (PRME) as its framework, with the United Nations Sustainable Development Goals (UNSDGs) serving as metrics for program and course outcomes. Our study examines teaching and learning practices, curriculum development, and policies worldwide, using secondary sources and publicly available data. The Holistic Stewardship Framework aligns with research emphasizing the role of responsible leadership in enhancing knowledge sharing and organizational performance. It addresses the need for interactive learning approaches fostering critical thinking and creativity. Practical examples demonstrate how integrating UNSDGs into courses equips future managers to navigate complexity, ethical dilemmas, and global challenges. This paradigm bridges theory and practice, cultivating leaders who balance economic viability with social responsibility and environmental stewardship. It represents a comprehensive shift in management education, preparing business leaders to thrive in a dynamic, interconnected world and address 21st-century challenges. Keywords: holistic stewardship framework, responsible management education, sustainable development goals, management education, responsible leadership